Assisted Suicide and Reproductive Freedom: Exploring Some Connections - Susan Frelich Appleton (Washington University Law Quarterly, 1998)
The connections between these issues are sure to be explored anew now that the Supreme Court has decided Washington v. Glucksberg and Vacco v. Quill, rejecting both due process and equal protection challenges to assisted suicide bans while purporting to leave undisturbed existing abortion precedents. This Article takes a brief look at three particular connections between the assisted-suicide cases and reproductive freedom. Part I examines the two-part test for substantive due process protection articulated in Glucksberg and raises questions about what this test might mean for the future of reproductive freedom. Part II, which considers Quill's reinforcement of the traditional distinction between omissions and actions, reviews the feminist critique of the omission-duty principle. This Part also shows how variable understandings of "omission" and "action" have allowed the Court both (a) to constrict abortion rights in the abortion-funding cases and their aftermath and (b) to overlook a persuasive argument for abortion freedom, the samaritan argument. Part III explores Glucksberg’s conclusion that the debate on assisted suicide should continue, emphasizing the possible consequences for reproductive autonomy of the Court's implicit suggestion that Congress might ultimately resolve this debate. Throughout, this Article reveals how the Court's analysis in Glucksberg and Quill overlooks-not necessarily inadvertently-important implications for reproductive rights.
Keywords: Assisted suicide; Abortion; Right of privacy; Human reproduction